Characterisation of knitted conductive textiles for wearable motion sensor applications - Isaia, Cristina (2018)
Combining stainless steel with polyester fibres adds an attractive conductive behaviour to the yarn. Once knitted in such a manner, fabrics develop sensing properties that make them suitable for wearable applications as a consequence of the variation of their conductivity when subject to structural deformations. The use of such textiles as accurate strain/motion sensors can be considered the new frontier in wearable sensor applications, in opposition to their use as simple strain/motion detectors as mainly done until now.